2014
DOI: 10.1021/jp502825p
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Hybrid Nanomaterials from Water Dispersible CaF2:Eu3+, Mn2+ and Fe3O4 for Luminescence and Hyperthermia Application

Abstract: CaF 2 nanoparticles doped with 1 at. % Eu 3+ and codoped with Mn 2+ ions (1, 2, and 3 at. %) were synthesized at 180 °C by using ethylene glycol as a capping agent and solvent medium. The emission spectra of these nanomaterials show two main peaks at 590 and 612 nm after excitation at 240 or 394 nm. Enhancement in luminescence is found upon codoping of Mn 2+ . Parts of Eu 3+ ions are substituted into Ca 2+ sites (having a symmetry environment), which is reflected in the higher probability of magnetic dipole tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…Unlikely with excitation spectra of YVO 4 :2Dy which has the highest intensity peak at 320 nm (V-O CT); the hybrid shows the strongest peak at 300 nm which is assigned to exciton formation between YVO 4 :2Dy and Fe 3 O 4 interface. Such type of exciton formation was reported in some previous papers [8,22]. Here, we strongly believe that the peak normally observed at 320 nm is being canvassed by the strong exciton peak at 300 nm since after the formation of hybrid it is confirmed that both emission and excitation are lower than corresponding values of YVO 4 :2Dy but after the formation of hybrid peak at 300 nm is still remained as a strong peak from which it is concluded that it is generated from exciton.…”
Section: Hyperthermia Studysupporting
confidence: 79%
See 2 more Smart Citations
“…Unlikely with excitation spectra of YVO 4 :2Dy which has the highest intensity peak at 320 nm (V-O CT); the hybrid shows the strongest peak at 300 nm which is assigned to exciton formation between YVO 4 :2Dy and Fe 3 O 4 interface. Such type of exciton formation was reported in some previous papers [8,22]. Here, we strongly believe that the peak normally observed at 320 nm is being canvassed by the strong exciton peak at 300 nm since after the formation of hybrid it is confirmed that both emission and excitation are lower than corresponding values of YVO 4 :2Dy but after the formation of hybrid peak at 300 nm is still remained as a strong peak from which it is concluded that it is generated from exciton.…”
Section: Hyperthermia Studysupporting
confidence: 79%
“…Heat generation from eddy current is negligible compare to Brownian and Neel's which main component is for heat generation in the magnetic samples. The detailed studies of the heat generation during the hyperthermia had been reported elsewhere [8]. Heat generation from samples in terms of specific absorption rate (SAR) is given by the following relation.…”
Section: Hyperthermia Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The solid fluoride materials have drawn attention due to their unique properties, like low-energy phonons, high ionicity, electron-acceptor behaviour, high resistivity and anionic conductivity [6–8] and also have wide range of potential optical applications in optics, biological labels and lenses [9, 10]. Fluoride base system possesses very low vibrational energy comparing oxide-base system therefore quenching of excite states of the lanthanide ions is minimal in fluoride-based system [11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…The structural, morphological properties of QTF coated with Nanocrystalline ZnO using SILAR followed by CBD were examined by X-ray diffraction (XRD), Scanning Electron Microscopy (SEM) [8]. The XRD diffraction analysis is carried out using PANalytical (X'PERT-PRO) X-Ray diffractometer with cu Kα radiation (λ=1.54056 Ȧ).…”
Section: Characterization Studies Of Zno Coated Qtfmentioning
confidence: 99%